2019
DOI: 10.26504/rs87
|View full text |Cite
|
Sign up to set email alerts
|

Gender, pensions and income in retirement

Abstract: This report has been accepted for publication by the Institute, which does not itself take institutional policy positions. All ESRI Research Series reports are peer reviewed prior to publication. The author(s) are solely responsible for the content and the views expressed.Ensuring that women have the necessary skills to ensure their financial security in older age is crucial and requires an understanding of how financial decisions are made, and how men and women may differ in terms of financial decision-making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…Finally, the third pillar is a voluntary savings pillar, typically comprised of long-term personal savings and financial investments used to fund retirement over and above first and second-pillar arrangements. Private pension schemes are voluntary and include Retirement Annuity Contracts (RACs), commonly used by the selfemployed, and PRSAs, which were introduced in 2002 as an attempt to increase the pension coverage among low-coverage employee groups (Nolan et al, 2019).…”
Section: Chapter 2 Irish Pension Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the third pillar is a voluntary savings pillar, typically comprised of long-term personal savings and financial investments used to fund retirement over and above first and second-pillar arrangements. Private pension schemes are voluntary and include Retirement Annuity Contracts (RACs), commonly used by the selfemployed, and PRSAs, which were introduced in 2002 as an attempt to increase the pension coverage among low-coverage employee groups (Nolan et al, 2019).…”
Section: Chapter 2 Irish Pension Systemmentioning
confidence: 99%
“…While this was initially intended to be fully rolled out for those retiring in 2020 onwards, those reaching the SPA are currently being assessed under the existing and TCA systems and given an entitlement corresponding to the higher of the two.8 The maximum contributory state pension payable in 2010, when wave 1 of the TILDA dataset was collected, was €230.30 per week, corresponding to 33.1 per cent of average earnings (using the CSO Earnings and Labour Costs measure of average earnings). The non-contributory state pension is means-tested and was capped at a pre-tax rate of €219 per week in 2010(Nolan et al, 2019).9 The effective retirement age is the average age of labour market exit. It is generally lower than the state pension age (SPA) (OECD, 2019).…”
mentioning
confidence: 99%
“…Although amongst employees, pension coverage (including occupational pension coverage from current and previous employments, and personal pensions), for men and women is fairly similar (57.1% and 55.4%, respectively) (CSO, 2019a) overall, using data from the 2014 Survey on Income and Living Conditions (SILC), Collins (forthcoming) found that men contribute between 30 and 35% more than women to their private pension (with that gap persisting across earners in most age groups). Furthermore, amongst retired people, 55% of retired men receive a private or occupational pension, compared to only 28% of women (Nolan, Whelan, McGuinness, & Maître, 2019).…”
Section: Women and Pensions In Roimentioning
confidence: 99%
“…Jerry Moriarty, chief executive of the Irish Association of Pension Funds, stated that the pensions sector had been “crying out” for simplification in the ROI (Reeve, 2018). This was deemed to be especially important due to low levels of financial literacy and numeracy (Nolan et al, 2019). This can lead to financial decisions being made which are not consistent with financial needs (Lusardi & Mitchell, 2014).…”
Section: Proposed Automatic Enrolment In the Roimentioning
confidence: 99%
See 1 more Smart Citation